Low-contrast visual acuity test is associated with central inflammation and predicts disability development in newly diagnosed multiple sclerosis patients - Dolcetti, Ettore; Buttari, Fabio; Bruno, Antonio; Azzolini, Federica; Gilio, Luana; Di Caprio, Veronica; Lauritano, Gianluca; Borrelli, Angela; Galifi, Giovanni; Furlan, Roberto; Finardi, Annamaria; Musella, Alessandra; et al. (Frontiers in Neurology, 2024)
The visual system is a prominent site of damage in MS since the earliest phases of the disease. Altered low-contrast visual acuity (LCVA) test has been associated with visual impairment and retinal degeneration, predicting medium-and long-term disability. However, it is unclear whether LCVA may also represent a reliable measure of neuroinflammation and a predictor of disease evolution in the very early stages of MS. We explored in a group of 76 consecutive newly diagnosed relapsingremitting MS (RR-MS) patients without visual impairment or altered visual evoked potentials, the association between LCVA scores at 2.5% and 1.25% and clinical characteristics, including prospective disability evaluated after one-and two years of follow-up. Associations between LCVA and the CSF levels of IL-10 at diagnosis were also analyzed.A negative correlation was found between LCVA at 2.5% and Expanded Disability Status Scale (EDSS) evaluated at first (Spearman's Rho = -0.349, p = 0.005, n = 62) and second year (Spearman's Rho = -0.418, p < 0.001, n = 62) of follow-up, and negative correlations were found with Multiple Sclerosis Severity Score (MSSS) at first (Spearman's Rho = -0.359, p = 0.004, n = 62) and second year (Spearman's Rho = -0.472, p < 0.001, n = 62). All the data were confirmed by a mixed effect model, considering other clinical variables. A positive correlation was found between the CSF concentrations of IL-10 and LCVA at 2.5% (Spearman's Rho = 0.272, p = 0.020, n = 76), and 1.25% (Spearman's Rho, = 0.276, p = 0.018, n = 76), also evidenced in a linear regression.In MS patients at diagnosis, altered LCVA may be associated with CSF inflammation and represent a useful parameter to identify patients with worse disease course.